Psychometric properties of the Sinhala perceived stress questionnaire (PSQ8-11) in Sri Lankan primary school children - Peiris, D. L. I. H. K.; Duan, Yanping; Vandelanotte, Corneel; Liang, Wei (Frontiers in Psychology, 2024)
Background: Stress influences examination performance among Sri Lankan students. Validated tests are required to evaluate stress levels among elementary students in Sri Lanka. Therefore, the Perceived Stress Questionnaire 8-11 (PSQ8-11) was translated into a Sinhala version. The aim of this study was to examine the psychometric properties of the translated and adapted scale among elementary level school children in Sri Lanka and examine invariance across male and female children. Methods: The participants were 1021 students from seven schools. After removing missing values, responses from 693 students (mean age = 9.65 ±.478 years, 51.8% male) were analysed for participant characteristics. Cronbach's alpha, Spearman's correlation, and confirmatory factor analysis with measurement invariance models were conducted after adding one item to the original PSQ8-11 version. Results: The Cronbach's alpha value for the 20-item modified PSQ8-11 Sinhala version was.788. The two subscales, psychological stress (Cronbach's alpha =.615) and physiological stress (Cronbach's alpha =.711), indicated a satisfactory level of internal consistency. Furthermore, a statistically significant correlation (p < 0.01; 2-tailed) was reported among each of the subscales. Confirmatory factor analyses demonstrated a satisfactory goodness-of-fit across the two models by confirming the theoretical constructs of the PSQ8-11 translated version with its two subscales. The two-factor model has better model fit indices compared to the unidimensional model (χ 2 /df = 1.447, CFI =.947, TLI =.938, WRMR =.028, RMSEA =.026, SRMSR =.0341, and PCLOSE = 1 of the twofactor model). Gender groups were variant at the model level (DiffChiX 2 (29.941)/20), P =.071). Conclusion: Acceptable psychometric properties for the PSQ8-11 Sinhala version were observed in elementary schoolers in Sri Lanka.